A comprehensive influenza reporter virus panel for high-throughput deep profiling of neutralizing antibodies - Adrian Creanga (Nature Portfolio, 2021)
Understanding the human antibody response to influenza A virus strains is important for vaccine development. Here, Creanga et al. generate a panel of 55 replication-deficient reporter viruses representing diversity of human H1N1 and H3N2, and pandemic subtypes and characterize the neutralization profile of 24 antibodies and polyclonal sera.